American philosophy before pragmatism - Goodman, Russell B. (Oxford Oxford University Press, 2015)
Russell B. Goodman tells the story of the development of philosophy in America from the mid-18th century to the late 19th century. The key figures in this story, Jonathan Edwards, Benjamin Franklin, Thomas Jefferson, the writers of The Federalist, and the romantics (or 'transcendentalists') Emerson and Thoreau, were not professors but men of the world, whose deep formative influence on American thought brought philosophy together with religion, politics, and literature. Goodman considers their work in relation to the philosophers and other thinkers they found important: the deism of John Toland and Matthew Tindal, the moral sense theories of Francis Hutcheson, Adam Smith, and David Hume, the political and religious philosophy of John Locke, the romanticism of William Wordsworth and Samuel Taylor Coleridge, and the transcendental idealism of Immanuel Kant.-- Source other than Library of Congress.
Jonathan Edwards -- Benjamin Franklin -- Interlude : strands of Republican thought -- Thomas Jefferson -- Ralph Waldo Emerson -- Henry David Thoreau -- Epilogue : some continuities in American philosophy.
Includes bibliographical references and index.
Keywords: Philosophy, American -- 18th century; Philosophy, American -- 19th century